Bezpieczeństwo i ochrona w usługach logistycznych - Kubicki, Jerzy (Safety and Protection in Logistic Services, 2008)
The development of the role, rank and importance of logistic services in the flows of goods, services and information within the economic activities in the regional, international and global scales created the base for new concepts of application of logistic and realisational concepts of logistic services. Spatial and time structure developments in logistic operations resulted in the growth of complexity of logistic supply chains, the multi subject structures of logistic operations and the changes in internal and external conditions of conducting of logistic services. Within the factors of competitiveness of logistic services the crutial role is for quality ones, with special reference to the safety of delivery and the security of delivery. Lacking international regulations related to standards of logistic services and complex logistic services resulted in different understanding of the duties of logistic operators and the safety and the security of delivery processes. These delivery chains which are conducted under existing international regulations (land-sea logistic delivery chains and land-air logistic delivery chains), found their solutions related to the safety and security obligations. These logistic delivery chains which didn't find their international regulatory basis (land logistic delivery chains in the systems of intermodal and multimodal nature) may meet serious problems in adaptation to the requirements of the safety and security in logistic operations. The paper presents the problems of adaptation of logistic operations in the land areas of operations, considering potential and existing possibilities to solve the questions of safety of logistic chains (safety management in logistic delivery chains), as well as security of logistic chains (implementation of the security systems in logistic operations).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 316-327